2016
DOI: 10.1155/2016/8901253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Properties on Adhesion Forces and Attachment ofStreptococcus mutansto ZirconiaIn Vitro

Abstract: Zirconia is becoming a prevalent material in dentistry. However, any foreign bodies inserted may provide new niches for the bacteria in oral cavity. The object of this study was to explore the effect of surface properties including surface roughness and hydrophobicity on the adhesion and biofilm formation of Streptococcus mutans (S. mutans) to zirconia. Atomic force microscopy was employed to determine the zirconia surface morphology and the adhesion forces between the S. mutans and zirconia. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 48 publications
4
52
1
2
Order By: Relevance
“…In previous studies, increased hydrophilicity of titanium surfaces was shown to reduce attachment of bacterial species like S. mutans while not affecting others like S. sanguinis. 45,46 In contrast, surface wettability was not observed to significantly affect the amount of bacterial attachment after 30 days of immersion in the present study, but the increased surface hydrophilicity of Ti-modSLA implants may have influenced the developing biofilm structure and subsequent corrosion features. However, differences in surface morphology between Ti-SLA, Ti-modSLA, and TiZr-SLA implants could not be attributed to differences in growth conditions as the optical density (OD 600 ) and pH of the immersion media for all implants remained the same throughout testing (data not shown).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In previous studies, increased hydrophilicity of titanium surfaces was shown to reduce attachment of bacterial species like S. mutans while not affecting others like S. sanguinis. 45,46 In contrast, surface wettability was not observed to significantly affect the amount of bacterial attachment after 30 days of immersion in the present study, but the increased surface hydrophilicity of Ti-modSLA implants may have influenced the developing biofilm structure and subsequent corrosion features. However, differences in surface morphology between Ti-SLA, Ti-modSLA, and TiZr-SLA implants could not be attributed to differences in growth conditions as the optical density (OD 600 ) and pH of the immersion media for all implants remained the same throughout testing (data not shown).…”
Section: Discussioncontrasting
confidence: 74%
“…in online Journal ). In previous studies, increased hydrophilicity of titanium surfaces was shown to reduce attachment of bacterial species like S. mutans while not affecting others like S. sanguinis . In contrast, surface wettability was not observed to significantly affect the amount of bacterial attachment after 30 days of immersion in the present study, but the increased surface hydrophilicity of Ti‐modSLA implants may have influenced the developing biofilm structure and subsequent corrosion features.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the forces involved in microbial adhesion, a multifunctional technique of atomic force microscopy (AFM) has been introduced (Dufrene & Pelling, ; Zhang, Aslan, Besenbacher, & Dong, ). AFM studies have shown that roughened substrate surfaces show significant enhancement in bacterial adhesion (Mei, Busscher, van der Mei, & Ren, ; Wang et al, ; Yu et al, ). Enamel surfaces etched by phosphoric acid are vulnerable to cariogenic bacteria; this is associated with an enhanced contact area and irregular grooves on the surface created by the dissolution of phosphoric acid (Buonocore, ; Zhu, Tang, Matinlinna, & Hagg, ).…”
Section: Introductionmentioning
confidence: 99%
“…AFM studies have shown that roughened substrate surfaces show significant enhancement in bacterial adhesion (Mei, Busscher, van der Mei, & Ren, 2011;Wang et al, 2015;Yu et al, 2016). Enamel surfaces etched by phosphoric acid are vulnerable to cariogenic bacteria; this is associated with an enhanced contact area and irregular grooves on the surface created by the dissolution of phosphoric acid (Buonocore, 1955;Zhu, Tang, Matinlinna, & Hagg, 2014).…”
mentioning
confidence: 99%
“…It is through this protein layer that oral bacteria attach to the resin and to tooth surfaces [45]. The adherence of early colonizers, for example, S. mutans , to the salivary pellicle is an initial step in biofilm formation.…”
Section: Emerging Approaches To Reduce Oral Biofilm Degradationmentioning
confidence: 99%